Your biosphere is my backyard: the story of Bosawas in Nicaragua - Kaimowitz, D.; Faune, A.; Mendoza, R. (Center for International Forestry Research, 2003)
Despite efforts to establish protected areas around the worl, the authority of government remains weak in forested areas. We examine the largest protected area in Central America, 'Bosawas' National Resource Reserve in Nicaragua, to demonstrate how overlapping systems of governance have encourage rapid ecology destruction and social differentiation, as well as corruption and violence. We conclude that Migdal's observation about forest governance is being guided by 'strong societies and weak states' (1998) is unlikely to change and must be the starting point for the future effortsin decentralized natural resource management.